An assessment of a Tsunami warning in South -East Bangladesh - Tasneem, Sakiba; Moushumi Chaudhury (BRAC Research and Evaluation Division (RED), 2020)
This research aims to look at household responses to a tsunami warning that took place in south-east coastal areas of Bangladesh on 12 September 2007. The study was conducted in both the mainland and islands of Coxs Bazar district. We examined the impact of the warming by measuring the effectiveness or the warming. reasons behind evaluation of failure to do so. experience or evacuating and staying in shelters. and loss in assets. We also examined whether evacuees will trust future warnings. The findings also reveal the extent to which people in the tsunami prone coastal areas have enough time to respond to a warning in the future. The findings in this study provide important information to help improve the effectiveness or tsunami warning in the future.